Análisis de la incidencia de (Bactericera Cockerelli) en la provincia de Cotopaxi en los cantones (Salcedo, Latacunga, Saquisili, Sigchos, Pujili). - Moreno Muela, Brayan Stalin (2023)
The purpose of this research work was to analyze (Bactericera cockerelli) incidence at Cotopaxi province, (Salcedo, Latacunga, Saquisili, Sigchos and Pujili) cantons, on potato and tree tomato producing areas of these cantons, For this purpose, a database of Agrocalidad was taken, where a frequency analysis was performed in order to obtain (Bactericera cockerelli) incidence with the help of the Infostat program, and a multivariate analysis of principal components was performed to identify the relationship between variables. After performing all these analyses, it was determined that the canton with the highest percentage of (Bactericera cockerelli) incidence was Latacunga with 55%, other cantons had a lower percentage such as Salcedo with 29%, Pujili with 12%, Saquisili and Sigchos had a percentage of 2% each. It was proceeded to identify critical points for purple top disease (Candidatus Libericater), transmitted by Bactericera sp. in the potato and tree tomato producing areas, which were Pujili center with 92% belonging to Pujili canton, Chantilin with 80% belonging to Saquisili canton, San Miguel with 37% belonging to Salcedo canton, Belisario Quevedo with 35% of incidence belonging to Latacunga canton.